EFFECT OF AQUEOS EXTRACT OF Momordica balsamina AND Cucumis metuliferus FRUITS ON NEWCASTLE DISEASE IN PULLETS - Salisu, Usman Shehu; Garba, Muhammad Ghazali; Sabo, Mustapha Nalado; Jamilu, Runka Yahaya; Zaharadeen, Ayuba Sullubawa; Sanusi, Ahmad Zakariyau; Babashani, Mohammed; Lawal, Mariya (FUDMA Journal of Sciences, 2020)
The study was conducted to determine the effect of aqueous extract of Mormordica balsamina and Cucumis metuliferus fruits on Newcastle disease (NCD) in pullets. Ninety (90) pullets were used for the study. The pullets were divided into prophylactic and curative groups comprising 10 birds per group. For prophylactic groups aqueous extract of the fruits at concentration of 2.5g and 5.0g per 100litres of water were given to the pullets ad-libitum for two weeks and then challenged with Newcastle disease virus kudu 113 strain via intra ocular route while for curative groups the pullets were challenged with the virus and then treated with the aqueous extracts of the fruits at 2.5g and 5.0g per 100litres of water ad-libitum. Data collected were analyzed using one way analysis of variance (ANOVA) using Statistical Analysis Software version 9.1. The results showed that M. balsamina at 2.5g/100litres of water had very good curative abilities which recorded lower clinical signs, mortality, postmortem lesions, higher antibody titer and higher white blood cell activity with a statistically significant (p
Keywords: Newcastle disease, Mormordica balsamina, Cucumis metuliferus, pullets